Can Domestic Policies Influence Inflation? - Mody, Ashoka; Ohnsorge, Franziska (Washington, D.C. : International Monetary Fund, 2007)
Globalization operates not only by reducing domestic pressures on inflation but also by reducing the scope of domestic authorities to influence the pace of inflation. First, as markets are integrated, the common, cross-border sources of inflation increase, reducing the extent of domestically-generated inflation. Based on a methodology identifying common time and sectoral trends, we find this to be especially the case in the countries of the eurozone, with their longer histories of product market integration. Second, even the domestically-generated component of inflation may be difficult to manipulate. Policies act, especially in the shortrun, through managing domestic demand. But the relationship between domestic demand (proxied by the output gap and unit labor cost growth) and inflation has been weak, constrained in part by trade openness. Moreover, the domestic component of inflation contains a country-specific international catch-up process that generates price equalization across countries. The evidence is that catch-up has accelerated with increasing market integration. Thus, for the eurozone economies, there may be limits on the use of fiscal and labor market policies to contain inflation. The new member states may not have policy leverage to meet the Maastricht inflation limit necessary for entering the eurozone. Casestudies show that fiscal consolidation needed to comply with the inflation criterion can be large and sustained only briefly to get under the Maastricht wire.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet